ANALISIS KERUNTUHAN LERENG DAN SOLUSI PERBAIKANNYA PADA BANGUNAN SPBU SAMBIPITU - KABUPATEN WONOSARI - Nasibu, Rito (Sainstek, 2010)
The building of Sambipitu Gas Station had collapse after the heavy rain in November 2000 and operates recently during one month after the building had rebuilt up. Area condition was congeries land of the area by the side of slope. Based on the data analysis result, it was found that the main reason of the collapse was the unstable of land restraint wall. It was caused by the design of foundation dimension that not good and the construction that was low-grade. In addition, the descent of the congeries in the back of wall by water permeation from the surface and land-watercourse caused the unstable of land restraint wall. Therefore, it solidifies the congeries of the back of wall pair and effect to the fracture by the outside of wall that was piping. This piping flow the land water that collapses the yard and caused the difference of office building descent in foundation side of near yard that collapse. The solution that was suggest was improve the construction quality in field and attend to the method with priority scales of which work that has to be first in order it doesnt risk the following work, considering the gas station work consist of some works such as civil building, mechanic, electric and the utility of other supporting buildings. Keywords: landslide, piping, construction quality